Addressing the negative impact of consumerism on young people by (re)awakening their spirituality through sense of place - Ontong, K. (South African Journal of Higher Education, 2020)
Consumerism holds the view that personal wellbeing and happiness depend largely on the material goods a person can buy (Dwyer 2007). Advertising constantly bombards our youth with images of materially seductive things. The impression given is that the right consumer goods will lead to a fulfilled life. However, the life experience of most young people is in stark contrast with what they should want as advocated by the consumption norms of society. It is often these contrasts that lead to feelings of inadequacy, lack of desirability and an inability to recognise one’s own worth. I argue that one way of addressing these feelings among young people is by (re)awakening their spirituality, starting at school. However, spirituality in education is a potentially contentious area and educators tend to shy away from it (De Klerk-Luttig 2008). I therefore suggest a pedagogy of place with specific reference to sense of place, as an avenue for reawakening students’ spirituality. I draw on the works of spirituality by Kessler (2000) and Webster (2004) and sense of place (Ardoin, Shuh, and Gould 2012) to provide a renewed, integrated framework.